Análisis morfológico del esqueleto del zorro Andino (Lycalopex Culpaeus). - Morales Regalado, Jacqueline Raquel (2023)
The Andean fox (Lycalopex culpaeus) is a canid, which stands out among the other South American fox species for being one of the largest and having a dolichocephalic skull, for its analysis a comparison was made with a canine (canis lupus familiaris) with the same type of skull; since currently the morphological study of this species (lycalopex culpaeus) does not exist, and by comparing it with the canine (canis lupus familiaris) we were able to establish characteristics of importance for the study, which make this species unique. The general objective of the project was to analyze the skeletal morphology of the Andean fox (Lycalopex culpaeus) in comparison with a dolichocephalic canine (Canis lupus familiaris), by using a skeleton of each species to identify the unique characteristics of the Andean fox (Lycalopex culpaeus). For the taking of measurements, cranial, caudal or proximal and distal points were established, depending on the type of bone to be treated. Obtaining measurements of both length and width that are useful for the comparison between these two species. Significant differences were obtained in the skull, thoracic locomotor limb and pelvic locomotor limb; where the most significant differences were in the upper and lower jaw, which provides a better bite to the animal, helping it with its feeding development. In the frontal bone, due to its cranial part, it was observed that it is more stylized and elongated, thus achieving an arciform shape in the occipital protuberance. The skeletons of both the Andean fox (Lycalopex culpaeus) and the dolichocephalic canine (Canis lupus familiaris) are similar in many aspects. Both have dolichocephalic skulls, belong to the same family canidae, their bone structures are very similar, and the characteristics that differentiate them are minimal. We conclude by demonstrating that the measurements obtained from the bones of the Andean fox (Lycalopex culpaeus) compared with those of a dolichocephalic canine (canis lupus familiaris) did not differ much from each other, giving rise to what is mentioned in the scientific rationale that this species of fox is the largest of the South American foxes.